Comparing the Effectiveness of Solution-Focused Brief Therapy and Schema Therapy on Identity Styles and Social Anxiety in Adolescents - Piryaei , Neda; Mansoobifar , Mohsen; Ataeifar, Robabeh; Bahrami Hidaji , Maryam; Peymani, Javid (Applied Family Therapy Journal (AFTJ), 2023)
Aim: This research was conducted with the aim of comparing the effectiveness of Solution-Focused Brief Therapy and schema therapy on identity styles and social anxiety in students. Method: The current research was in terms of practical purpose, in terms of the nature of the semi-experimental research with a pre-test-post-test design with two experimental groups and a control group, and in terms of the type of data, it was quantitative. The statistical population included second grade high school students in Alborz province in the academic year 2018-2019, 60 of whom were selected as a statistical sample by staged cluster sampling and divided into two experimental groups and one control group (20 people for each group) were replaced. In order to collect data, standard questionnaires of social anxiety (Kanor et al., 2000) and identity style (Brzezunsky, 1992) were used. After completing eight sessions Solution-Focused Brief Therapy and eight group schema therapy sessions in the experimental groups, the mentioned questionnaires were completed again immediately and after three months respectively as a post-test and follow-up in the groups. The data was analyzed using variance analysis with repeated measurements through SPSS-V21 software. Results: Data analysis was done in descriptive and inferential statistics (analysis of covariance, analysis of variance with repeated measures and dependent t) through Spss-V21 software. The findings showed that there was a difference between the effectiveness of Solution-Focused Brief Therapy and schema therapy on students’ identity styles over time, and these treatments were stable over time. Also, there is a difference between the effectiveness of Solution-Focused Brief Therapy and schema therapy on students’ social anxiety over time, and Solution-Focused Brief Therapy was more effective than schema therapy in social anxiety variable. Conclusion: According to the results, the above-mentioned therapy can be used as a psychological intervention to reduce students’ body image concerns and social anxiety.